Pencegahan Pencoklatan Umbi Ubi jalar Untuk Pembuatan Tepung: Pengaruh Kombinasi Konsentrasi Asam Askrobat dan Sodium Acid Pyrophosphate - Kumalaningsih, Sri; Harijono, Harijono; Amir, Y. F. (Jurnal Teknologi Pertanian, 2004)
The research was conducted to find out the best combination of  ascorbic acid and SAPP concentration to prevent browning reaction to improve the appearance of sweet potato flour. A Completely Randomized Block Design with two factors was carried out. Ascorbic acid concentration of 1.00;2.00; and 3.00% as the first factor and SAPP (sodium acid poly phosphate) concentration ( 0.001; 0.01; and 0.1%) as the second factor. Both were dissolved in boiling water containing 0.6g/L citric acid. The best result of the combination was used for making sweet potato flour. The results showed that increased concentration of either ascorbic acid or SAPP reduced the browning reaction. But there was no interaction between treatment. The highest effectivity index (5.39) was showed by the addition of 2.00% ascorbic acid and 0.1% SAPP which reduced the rate of browning reaction with an R2 = 0.7997. Conversely, untreated sliced root showed a faster browning reaction with the R2 = 0.8621 after delaying the sliced tuber for 12 hours. There was a significant difference in flour lightness. The treated   root   has    L =   79,67     and untreated root has L = 77,46.   Keyword: sweet potato flour, browning reaction, ascorbic acid, Budidaya tani